FORMATION OF REFERENCE SECTIONS COLLECTION FUNDS AS AN INSTRUMENT OF THEIR CONSERVATION - Anfimova, G. (Visnyk of Taras Shevchenko National University of Kyiv. Geology, 2025)
Stratotypes and reference sections, that have great scientific and educational value, should be preserved. There is a need to preserve the reference sections both on location, in situ, and ex situ, on the basis of museums. The purpose of article is to develop the organization of reference sections conservation by Museum means on the example of the Mountainous Crimea Mesozoic stratotypes and the reference sections lithological and paleontological fund formation. The Mountainous Crimea stratotypes and reference sections preservation on the basis of the Museum is considered for the first time. Methods of field observations, description, comparison, analysis through the prism of the Museum research work, scientific and stock work, exhibition work are applied. The Geological Museum of the National Museum of Natural History (NMNH) NAS of Ukraine collections analysis for completeness of the various regions and age ranges representation in the structure of the Museum’s collection highlighted the gaps in the Mountainous Crimea representation. During the field works of 2011, 2012, 2015 the collection of 221 storage units was assembled. The number of samples in the collection is 854, among them fauna – 275. These samples represent 30 suites and 26 strata (43 and 37 accordingly) distinguished in the Mountainous Crimea Mesozoic deposits. Features of sampling and the collection description are as follows. (1) Sampling of main lithological-petrographic rock types, which represent the section. (2) Sampling from standard sections rocks which are of particular geological interest, as well as the samples that have the attractiveness and expressiveness characteristics. (3) Every object of lithological collection has duplicate samples. (4) For the first time in the Geological Museum of NMNH NAS of Ukraine in the process of collecting the 100% GPS reference and photographs of samples are made. (5) Instrumental lithological studies haven’t been carried out, the samples characteristic is presented at the level of macro description. (6) Remarkable feature of many of stratotypes and reference sections is that they act as locations of a number of minerals. (7) Following the desire for the continuity of the lithological and fauna samples showing, for the completeness of the section layers representation, if possible, we also gathered fossils. By creating a lithological and paleontological fund of the Mountainous Crimea standard sections the methods for their conservation on the basis of Natural History museums are developed.